Optical response of plasmonic nanostructures composed of coupled gold nanodisks. - Najah, S.; Jarmoumi, Y.; Akouibaa, A.; Fassi, S. El; Derouiche, A.; Ridouane, H. (IJRDO-Journal of Applied Science, 2016)
Due to the coupling effect of Surface Plasmon Resonance (SPR) excited by the incidentelectromagnetic wave, the gold nanodisks structures show special optical properties that can beapplied in many fields of nano-technology. In this work, a model based on the finite elementmethod (FEM) is developed to investigate the effect of the relevant parameters on the opticalproperties of gold nanodisks. The study is performed for various possible configurations, one,two, three and four gold nanodisks when they are aggregating in dielectric medium. Based onthe accurate geometric parameters, we plotted the numerical results of the resonance energy invarious conditions involving gap distance and radius of nanoparticles.